2013
DOI: 10.1371/journal.pone.0060412
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of Advanced Care Planning in Early Dementia (ACP-ED)

Abstract: BackgroundEnd-of-life-care is often poor in individuals with dementia. Advanced care planning (ACP) has the potential to improve end-of-life care in dementia. Commonly ACP is completed in the last six months of life but in dementia there may be problems with this as decision-making capacity and ability to communicate necessarily decrease as the disease progresses. Choosing the right time to discuss ACP with people with dementia may be challenging given the duration of the illness may be up to nine years.AimsTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
195
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(199 citation statements)
references
References 15 publications
1
195
1
2
Order By: Relevance
“…17 However, data on the best timing of advance care planning discussions in patients with dementia are conflicting. One recent qualitative study suggested that patients with mild dementia find such discussions acceptable, 42 but another found that people with dementia had difficulty considering their future selves. 35 More generally, some studies have identified particular triggers for initiating these conversations, such as recurrence of cancer.…”
Section: How Can We Initiate Discussion?mentioning
confidence: 99%
“…17 However, data on the best timing of advance care planning discussions in patients with dementia are conflicting. One recent qualitative study suggested that patients with mild dementia find such discussions acceptable, 42 but another found that people with dementia had difficulty considering their future selves. 35 More generally, some studies have identified particular triggers for initiating these conversations, such as recurrence of cancer.…”
Section: How Can We Initiate Discussion?mentioning
confidence: 99%
“…Staff confidence or lack of confidence was also identified as a key factor, but for brevity, we have not described this theme as it is well documented in the literature. 16,21,22…”
Section: Interviewsmentioning
confidence: 99%
“…Angehörige können sich auf den zu erwartenden Verlauf einstellen, einer Überforderung kann ein Stück weit vorgebeugt werden und die Wahrscheinlichkeit des Einforderns nicht mehr sinnvoller therapeutischer Maß-nahmen sinkt bei gleichzeitig besserer palliativer Versorgung der Patienten im Spätstadium. Der Tod des Patienten wird trotz der schweren Erkrankung häu ger als ein guter empfunden, wenn auf die skizzierte Weise Vorsorge betrieben worden ist [8,22,24,25,26,27].…”
Section: Vorteile Des Advance Care Planningunclassified